Pengaruh Pola Asuh Orang Tua Single Parent terhadap Tingkat Perkembangan Anak di Wilayah Panti Asuhan Balita Sehat Muhamadiah Kota Bandung - Eli Lusiani; Sella Febrita; Nunik Ayu Elvira (Syntax Corporation Indonesia, 2024)
This study aims to determine the influence of parenting style of Single Parents with the development of children aged 3-6 years. The research design uses quantitative descriptive methods, sampling using total sampling techniques with the number of samples obtained as many as 80 respondents. Data collection was carried out by distributing parenting questionnaires and observing children's development using the KPSP Questionnaire. Technical analysis using SPSS, to determine the effect of maternal parenting on the development of children aged 3-6 years with the rho sperman formula. The results showed Democratic Parenting 62.5%, Authoritarian Parenting 25%, Permissive Parenting 12.5%. The development is at the corresponding status of 56.25%. This study states that there is a significant relationship between the parenting style of single parents on the development of children aged 3-6 years with the results of V Palue 0.008. Recommendation: Improving Single Parents Parenting in Implementing Spiritual Care for Children.